Brookes on modern dancing, containing a full description of all dances, as practised in the ball room and at private parties, together with an essay on etiquette. - Brookes, L. De G. (Laurence De Garmo) (New York [The author], 1867)
The format for this manual is typical of nineteenth-century dance treatises. It begins with a short discussion on the utility of dancing, followed by a section devoted to etiquette of the ballroom and how to give balls. Descriptions of dances in this manual include quadrilles, waltz, polka, polka redowa, schottisch, polka mazurka, varsovienne, and the waltz in 5/4. The book concludes with eighty-seven cotillon figures and eight pages of ballroom dance music.
Includes music.
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Ballroom dancing -- Handbooks, manuals, etc; Dance music; Dance Instruction and Technical Manuals; Music for Dance